Exploring the Perceptions of Malaysian Employers Towards Hiring Ex-Offenders - Nee, Wong Yuen; Nee, Wong Yuen; Kartar Singh, Jugindar Singh; Kularajasingam, Janitha (Journal of Public Administration and Governance, 2022)
There is much support for hiring ex-offenders, but employers are unwilling to hire ex-offenders due to several reasons. In Malaysia, there is a paucity of research exploring employers’ perceptions toward hiring ex-offenders. This qualitative study aimed to collect in-depth data from employers on their perception of hiring ex-offenders in Malaysia. In addition, the employers also stated their views on how support can be provided to the ex-offenders. This study was based on interpretivism philosophy, and an inductive approach was considered more appropriate. In this qualitative study, data in words and voice was collected from eight employers by using semi-structured interviews. A thematic analysis was carried out to identify the themes that emerged from the collected data. The first question explored employers’ perception of hiring ex-offenders, and the themes that emerged encompass rationale, perceived risk, the severity of crime, skills and knowledge and personal characteristics. The themes showed that hiring decisions are conditional. On the second question concerning the support, the three themes that emerged include fair treatment, mental support, and financial support. The study results provide an understanding to employers and HR managers on the perceptions of hiring ex-offenders into the workplace and providing support.